Pengaruh Office Channeling dan Dana Pihak Ketiga terhadap Laba dengan Pembiayaan Sebagai Variabel Intervening pada Perbankan Syariah di Indonesia - Muhammadinah Muhammadinah (Iqtishodia: Jurnal Ekonomi Syariah, 2020)
This study aims to determine the influence of office channeling and third party funds to profit with financing as a variable intervening on sharia banking in Indonesia. The population in this study is the entire sharia banking in Indonesia consisting of 14 Sharia commercial banks and 20 Syariah business units. The sample used is the summary of Sharia banking financial statement period of 3 years on a monthly basis so that the number of samples as much as 36. The analytical technique used is Path analysis using T Test , where the mediation test is done with the procedure developed by Sobel (1982) and known as Sobel Test. The finding show that the office channeling variable had a direct and insignificant effect on the financing variable at Islamic banking profit in Indonesia, while the third party fund variable directly had a significant effect on the financing variable.